Fiscal condition of the public sector in Brazil: An analysis with an emphasis on the states in the North and Northeast regions of the country and on financing for rural development - Rodrigo Octávio Orair; Sérgio Wulff Gobetti; André Amorim Alencar; Jo\~ao Marcelo (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
The goal of this study is to evaluate the fiscal condition of the Brazilian public sector, focusing on the situation of state governments in the North and Northeast regions of the country and on international financing for rural development. The paper comprises six sections, including this introduction. Section 2 presents a broader view of the fiscal condition of the public sector, featuring consolidated fiscal indicators from each of the three government levels (central, state and municipal). The analysis allows for the identification of tendencies in public finances from an aggregate and, therefore, non-detailed perspective. [...]
Keywords: 330; fiscal condition; public sector; Brazil; analysis; North region; Northeast region; financing; rural development